A novel, tomographic imaging probe for rapid diagnosis of fungal keratitis. (8th December 2017) - Lee, Min Hee; Wiedman, Gregory; Park, Steven; Mustaev, Arkady; Zhao, Yanan; Perlin, David S
Abstract: Fungal keratitis is a leading cause of ocular morbidity and blindness in developing countries. Diagnosing fungal keratitis currently relies on a comparative evaluation of corneal biopsy or scraping using a direct microscopy and culture results. These methods not only carry the risk of developing complications due to the invasive tissue sampling but also are largely limited by diagnostic speed and accuracy, making it difficult to initiate timely appropriate antifungal therapy. Therefore, rapid and noninvasive diagnostic tools are a pressing need for improved outcomes for fungal keratitis. Taking advantage of the highly specific fungal cell targeting properties of caspofungin, we have developed a fluorescent chemical probe with high selectivity against fungal pathogens. Utilizing fluorescence imaging technology, we have demonstrated a highly specific and sensitive detection of Aspergillus in a fungal keratitis model in mice as early as 5 min post-topical application of the probe. Our results indicate that a fluorescence-mediated platform can be used as a rapid (<10 min) alternative to conventional methods for detecting Aspergillus, and potentially other fungi, in fungal infections of the cornea.